2022
DOI: 10.1002/glia.24267
|View full text |Cite
|
Sign up to set email alerts
|

The astroglial and stem cell functions of adult rat folliculostellate cells

Abstract: The mammalian pituitary gland is a complex organ consisting of hormone-producing cells (HPC), nonhormonal folliculostellate cells (FSC) and pituicytes, vascular pericytes and endothelial cells, and putative Sox2-expressing stem cells. Here, we used scRNAseq analysis of adult female rat pituitary cells to study the heterogeneity of pituitary cells with a focus on evaluating the transcriptomic profile of the Sox2expressing population. Samples containing whole pituitary and separated anterior and posterior lobe c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…Within pituitary cell types, gonadotrophs specifically express several genes, including Lhb, Fshb, Gnrhr, nuclear receptor subfamily 5 group A member 1 ( Nr5a1 ), and secreted phosphoprotein 1 ( Spp1 ) and together with thyrotrophs also express glycoprotein hormones, alpha polypeptide gene ( Cga ) 8 , 25 . Here we analyzed the expression of these genes in pituitary glands from WT and DKO females and males (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within pituitary cell types, gonadotrophs specifically express several genes, including Lhb, Fshb, Gnrhr, nuclear receptor subfamily 5 group A member 1 ( Nr5a1 ), and secreted phosphoprotein 1 ( Spp1 ) and together with thyrotrophs also express glycoprotein hormones, alpha polypeptide gene ( Cga ) 8 , 25 . Here we analyzed the expression of these genes in pituitary glands from WT and DKO females and males (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using qRT-PCR analysis, we also showed the expression of these genes in pituitary tissue. Moreover, our recent single cell RNA sequencing of freshly dispersed rat pituitary cells revealed that Ptprn and Ptprn2 are well expressed in both female and male gonadotrophs, as well as other types of pituitary secretory cells and folliculostellate cells of both sexes 8 , 25 . Kubosaki et al 16 also reported that these genes are expressed in the pituitary gland, as shown by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…As well as unearthing cellular heterogeneity, from these types of data, we can infer cell-crosstalk based on transcript expression of known receptor-and ligandpairs. Analysis of these pairs throughout whole tissues Whole mouse pituitary 13,663 cells from 6 × 7 week male mice Fletcher et al [112] Rat anterior pituitary 6896 cells from 2 male and 2 female postpubertal rats Mayran et al [103] Mouse anterior pituitary 9269 cells from 1 male 4 month old mouse Cheung et al [110] Whole mouse pituitary 6492 cells from 1 × P4 female mutant mouse 6705 cells from 1 × P4 female control mouse Chen et al [113] Mouse intermediate and posterior pituitary lobes 528 cells from 1 × 3 month old male mouse Ho et al [114] Whole mouse pituitary 3532 cells from 1 × 13 week old virgin female 7614 cells from 2 × 13 week old lactating females 7443 cells from 4 × 8 week old male and females 2596 cells from 8 week old acromegalic female Zhang et al [108] Human fetal pituitary 4113 cells from 21 human fetuses Lopez J.P et al [115] Whole mouse pituitary 9,879 cells from 10 week-old male mice: 5 x unstressed and 5 x chronically stressed Moncho-Amor et al [116] Intermediate lobes of control and mutant mouse pituitaries 2110 cells from 3 month old control male and female mice 8832 cells from 3 month old mutant male and female mice Cui et al [117] Human neuroendocrine tumours 2679 cells from 21 human patients Ruf-Zamojski et al [70] Whole mouse pituitary 35,707 nuclei from 6 × 10-12 week old male and female mice Allensworth-James M et al [118] Whole mouse pituitary 18,301 cells from 6 x 8-week old diestrous female mice Vennekens et al [98] Anterior pituitaries of control and mutant mice 7977 cells from 9-11 weeks old control male mice 7000 cells from 9-11 weeks old mutant male mice 5278 cells from 14 month old control male mice 5860 cells from 14 month old mutant male mice Zhang et al [119] Whole chicken anterior pituitary 6733 cells from 6 male chicken and 9,919 cells from 6 female chicken both at 12 months Siddique et al [120] Whole adult teleost pituitaries 2592 cells from female teleost and 3804 cells from male teleost Fletcher et al [131] Whole rat pituitary 15,876 cells from 60 × 75 day -old female rats (Combined from; separated rat anterior pituitary, separated rat intermediate lobe and posterior pituitary, and whole rat pituitary) Zhang et al [121] Human pediatric, adult and aged pituitary 76,016 nuclei for snRNAseq 15,024 nuclei in the same-cell sn multiome (ATAC and RNA) Laporte E et al [122] Anterior pituitaries of control and mutant mice 9618 cells from control 2 × P7 mice 11,801 from mutant 2 × P7 mice was previously unachievable. In addition, the advent of single cell (or single nuclei) ATAC-seq has revolutionised the detail by which we can interrogate chromatin regulatory landscapes by measuring the...…”
Section: Deciphering Anterior Pituitary Signalling Centres Using Sing...mentioning
confidence: 99%
“…They also enable assessment of interactions between PSCs and other supporting cells such as endothelial cells and connective tissue. In a recent report, Fletcher et al [131] use CellChat to investigate WNT, BMP, Notch, and FGF signalling pathway interactions between the pituitary stem cells (referred to as folliculostellate cells), pericytes, endothelial cells and pituicytes in the postnatal rat pituitary. Interestingly they find Bmp2 and Bmp4, expressed by pericytes and endothelial cells, respectively, with their receptor transcripts (Bmpr1a and Bmpr2) enriched within PSCs [131].…”
Section: Epithelial-mesenchymal Interactions In the Pituitary Stem Ce...mentioning
confidence: 99%
See 1 more Smart Citation